ASME 2021 Conference on Smart Materials, Adaptive Structures and Intelligent Systems 2021
DOI: 10.1115/smasis2021-67752
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling and Simulation of a Soft Array of Dielectric Elastomer Actuators

Abstract: Dielectric elastomers (DEs) consist of thin membranes of dielectric material (e.g., silicone) coated with compliant electrodes. When subject to a high voltage, a DE undergoes an in-plane expansion which can be used for actuation purposes. Nowadays, most of the applications of DE actuators (DEAs) are based on single-degree-of-freedom systems. If many DEA elements are combined together in an array-like structure, a new generation of distributed and cooperative micro-actuators can be developed, with potential app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The electrical coupling arises when the Maxwell pressure acting on a DE, resulting from the application of an external electric field, induces a stress distribution which affects the mechanical response of the neighboring elements. This effect has already been studied experimentally in [43], and also validated with a model-based approach in [44]. In these works, it was shown that the electrical activation of one DE has generally a small influence on the reaction force of its neighbors.…”
Section: Single Membrane Dea-array Conceptmentioning
confidence: 68%
“…The electrical coupling arises when the Maxwell pressure acting on a DE, resulting from the application of an external electric field, induces a stress distribution which affects the mechanical response of the neighboring elements. This effect has already been studied experimentally in [43], and also validated with a model-based approach in [44]. In these works, it was shown that the electrical activation of one DE has generally a small influence on the reaction force of its neighbors.…”
Section: Single Membrane Dea-array Conceptmentioning
confidence: 68%
“…Based on the above COMSOL approach, Croce et al also developed a lumpedparameter version of the model [21,22], which will allow for the computationally efficient implementation of future cooperative control strategies (see Figure 6). Based on the above COMSOL approach, Croce et al also developed a lumped-parameter version of the model [21,22], which will allow for the computationally efficient implementation of future cooperative control strategies (see Figure 6).…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…Operating the DE afterwards in a strain range below the pre-stretch level unfolds the wrinkles, which, coupled with the extremely low electrode thickness of <20 nm, does not impact the stiffness of the DEA negatively (Figure 7a, top right), hence allowing for efficient actuation. Based on the above COMSOL approach, Croce et al also developed a lumped-parameter version of the model [21,22], which will allow for the computationally efficient implementation of future cooperative control strategies (see Figure 6).…”
Section: Electrodesmentioning
confidence: 99%
“…For the sake of this analysis, we consider a single DE membrane with the dimension defined in figure 9(a) (the same numerical values as discussed in section 3.1 are used), subject to a pre-stretch λ p = 1.10. For the simulations, the material parameters are chosen as in our previous work [53], while the boundary conditions are set equivalently to section 4.1.3. The membrane deformation is applied on the central portion of the active area as a prescribed displacement (9), and the reaction-force along the Z-axis is evaluated accordingly.…”
Section: Comparison With a Fully-coupled Three-dimensional Formulationmentioning
confidence: 99%
“…Because of the extremely high surface-tothickness ratio of the considered membrane (on the order of 10 5 m), the formulation presented in section 4.1 treats the DE as a thin membrane element, assuming that the electric field distribution is the same as in a parallel plate capacitor, and neglecting fringe electric fields (the latter assumption is also motivated by our previous studies in [53], in which we showed that fringing fields have a negligible impact on the overall array output). In this section, we validate these assumptions by comparing the predictions of the presented formulation with those of a fully-coupled three-dimensional formulation.…”
Section: Comparison With a Fully-coupled Three-dimensional Formulationmentioning
confidence: 99%